Suboptimization Model of Demand for Investment and Labor: An Optimal Control Theoretic Approach - Hiroki Tsurumi (Queen's University, Department of Economics, 1971)
The present paper is an attempt to extend Chetty's work. It derives a suboptimal adaptive control model for the demand for investment and labor by using invariant imbedding equations.
Keywords: 330